Perbudakan dalam Hukum Islam - Ahmad Sayuti Anshari Nasution (AHKAM : Jurnal Ilmu Syariah, 2015)
Islamic law emerged in the era of slavery. Slavery is one of the pillars which depends the economic life. Islam does not frontally abolish slavery. Islamic law provides solutions gradual liberation of slaves. Some illegal acts be sanctioned by an obligation to free a slave. Today, many practice similar to slavery. And this requires the completion of a solution in accordance with sharia corridor.DOI: 10.15408/ajis.v15i1.2852